2018
DOI: 10.1111/cxo.12656
|View full text |Cite
|
Sign up to set email alerts
|

Glaucomatous progression in the retinal nerve fibre and retinal ganglion cell‐inner plexiform layers determined using optical coherence tomography‐guided progression analysis

Abstract: The most common characteristic of RNFL and GCIPL progression determined using OCT-GPA was localised thinning in the inferotemporal area. Progression was more frequently found in the RNFL than in the GCIPL, and diffuse-type progression was more frequent in the GCIPL than in the RNFL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Our study offers a first hint that the pRNFL is altered in adulthood due to low birth weight. Furthermore, our finding of a thinner pRNFL, particularly in the inferior sector, may be relevant, as in glaucoma patients pRNFL changes manifest in the inferior sectors first 34 with a conspicuous ISNT rule, 35 leading to initial superior Bjerrum scotoma. 36 Additionally, progression of glaucoma is most frequently located in the inferotemporal sector of the pRNFL, 34 and pRNFL thinning is linked to several optic neuropathies.…”
Section: Discussionmentioning
confidence: 73%
“…Our study offers a first hint that the pRNFL is altered in adulthood due to low birth weight. Furthermore, our finding of a thinner pRNFL, particularly in the inferior sector, may be relevant, as in glaucoma patients pRNFL changes manifest in the inferior sectors first 34 with a conspicuous ISNT rule, 35 leading to initial superior Bjerrum scotoma. 36 Additionally, progression of glaucoma is most frequently located in the inferotemporal sector of the pRNFL, 34 and pRNFL thinning is linked to several optic neuropathies.…”
Section: Discussionmentioning
confidence: 73%
“…Our results are in agreement with a previous study that showed this progression pattern in the GPA trend analysis also occurs at earlier stages of the disease. 2 Although this pattern of trend analysis progression might not be unique to advanced disease, detection of progression is particularly difficult in advance disease, as we discussed in our article. Therefore, having the capability of detecting progression at this stage has important clinical implications worth emphasizing to practicing clinicians.…”
mentioning
confidence: 86%
“…In another study, Hwang et al 2 reported that, among the 42 progressed eyes with moderate-to-advanced stage glaucoma, trend-based OCT GPA showed progression only in 1 eye for RNFL and 13 eyes for GCIPL, which agrees with the results from Lavinsky et al However, when 64 progressed eyes with early stage glaucoma were evaluated, trend-based OCT GPA revealed similar patterns; progression was found only in 2 eyes for RNFL and 19 eyes for GCIPL. 2 This finding may suggest more frequent trend-based progression in GCIPL compared with RNFL may be explained by measurement modality rather than disease stage. The current OCT GPA algorithm from Carl Zeiss Meditec (Jena, Germany) is based on the changes in average or superior/inferior hemisphere thickness values for trend-based analysis and the change in thickness in each pixel area for event-based analysis.…”
mentioning
confidence: 89%
“…In the study by Lavinsky et al, 1 trend-based analysis of ONH parameters showed significant changes in advanced glaucoma. However, in the study by Hwang et al, 2 among the 106 eyes with OCT GPA progression either in RNFL or GCIPL, only 11 eyes showed progression in the average cupto-disc ratio by using trend-based OCT GPA (Hwang YH, unpublished data, August 1, 2018). This finding suggests that ONH progression analysis by OCT GPA may have limited value compared with RNFL or GCIPL analysis.…”
Section: Mm)mentioning
confidence: 99%
See 1 more Smart Citation